Speakable Wounds: Notes on a Miniature of the Huelgas Beatus - Lorenzo Rodríguez, Abel (Eikón / Imago, 2020)
The creation of alterity is built upon visible and invisible attributes. In the next article it will be explain one of the miniatures in Huelgas Beatus (Ms M.429, f. 94r) from marks or stigma with penal and religious origin. Specific, the ilumination on the openning of the Sixth Seal (Rev. 9:17–21) written on the dead bodies: Ubi occisa est tertia pars hominum. In order to explain this combination between graphic and visual system, it will draw on penal and theological traditions about the use of signs on the skin, like judicial confirmations.